Functional analysis of the sporulation-specific diadenylate cyclase CdaS in Bacillus thuringiensis - Zheng, Cao; Ma, Yang; Wang, Xun; Xie, Yuqun; Ali, Maria K.; He, Jin (Frontiers in Microbiology, 2015)
Cyclic di-AMP (c-di-AMP) is a recently discovered bacterial secondary messenger molecule, which is associated with various physiological functions. In Bacillus, the intracellular level and turnover of c-di-AMP is mainly regulated by three diadenylate cyclases (DACs), including DisA, CdaA and CdaS, and one c-di-AMP-specific phosphodiesterase. In this study, we demonstrated that CdaS protein from B. thuringiensisis is a hexameric DAC protein that can convert ATP or ADP to c-di-AMP in vitro and the N-terminal YojJ domain was essential for the DAC activity. Based on the markerless gene knock-out method, we demonstrated that the transcription of cdaS was initiated by the sporulation-specific sigma factor σH and the deletion of cdaS significantly delayed sporulation and parasporal crystal formation. These findings contrast with similar experiments conducted using B. subtilis, wherein transcription of its cdaS was initiated by the sigma factor σG. Deletion of all the three DAC genes from a single strain was unsuccessful, suggesting that c-di-AMP is an indispensable molecule in B. thuringiensis. Phylogenetic analysis indicated increased diversity of CdaS in the B. cereus and B. subtilis Bacillus subgroups. In summary, this study identifies important aspects in the regulation of c-di-AMP in Bacillus.